2015
DOI: 10.1111/bjdp.12112
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions in early childhood: The role of maternal and paternal parenting practices

Abstract: We investigated the association between mothers' and fathers' harsh parenting and sensitive parenting practices and child's executive functions (EF) in early childhood in 607 families. We focused on three broad dimensions of child EF: Emergent metacognition, inhibitory self-control, and flexibility measured with the parent-reported Behavior Rating Inventory of Executive Function-Preschool Version. Less sensitive parenting of the mother and harsher parenting of the father were related to lower scores of emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 75 publications
7
77
1
9
Order By: Relevance
“…Moreover, it is thought that parenting practices are of great importance for the socio-emotional and motivational development. Research (Lucassen et al, 2015) showed that the environment in which the child develops (including the style of parenting) influences the development of the prefrontal cortex and thus affects the development of executive functions. Research also indicates that parents of premature babies are often overprotective and see fewer strengths in the child than parents of children born at term.…”
Section: Health Psychology Reportmentioning
confidence: 99%
“…Moreover, it is thought that parenting practices are of great importance for the socio-emotional and motivational development. Research (Lucassen et al, 2015) showed that the environment in which the child develops (including the style of parenting) influences the development of the prefrontal cortex and thus affects the development of executive functions. Research also indicates that parents of premature babies are often overprotective and see fewer strengths in the child than parents of children born at term.…”
Section: Health Psychology Reportmentioning
confidence: 99%
“…Therefore, the role of fathers regarding the development of child executive functioning is important to examine. A study by Lucassen et al (2015) shows distinct effects of maternal and paternal parenting on child executive functioning. The authors found that less maternal, but not paternal sensitivity, and harsher parenting by fathers, but not by mothers, was related to lower scores on child executive functioning at 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…Their study specifically showed that perceived neglect was negatively correlated with measures of EF. Taking a closer look at parental care and EF in infants, toddlers, and preschool children, it can be assumed that there might be differences between father's and mother's sensitive and supportive parenting which, in turn, is correlated with EF (Towe-Goodman et al, 2014; Lucassen et al, 2015). …”
Section: Introductionmentioning
confidence: 99%